The approach to managing perinatal anxiety: A mini-review - Silverwood, Victoria Anne; Bullock, Laurna; Turner, Katrina; Chew-Graham, Carolyn A.; Kingstone, Tom (Frontiers in Psychiatry, 2022)
Perinatal Anxiety (PNA) is anxiety occurring during pregnancy and up to 12 months postpartum and is estimated to affect up to 20% of women. Risk factors for PNA are multiple and can be classed as psychological, social and biological. PNA negatively impacts on the mother, child and family. PNA is not well recognised and diagnosis of PNA can be challenging for clinicians. There is currently no validated case-finding or diagnostic test available for PNA. PNA has been less extensively researched than perinatal depression (PND). Clinical guidance currently recommends pharmacological and psychological therapies for the management of women with PNA, however the limited research available suggests that other intervention types may also be effective with some evidence on the effectiveness of non-pharmacological interventions in primary care for PNA. This article provides a mini-review of PNA, summarising current evidence around PNA including risk factors, the impact of PNA, the process of diagnosis of PNA and management options.